PENGARUH PENGETAHUAN HUKUM RIBA TERHADAP PENGGUNA SPAYLATTER TERHADAP AKAD JUAL BELI - Masrina Rahman (AN NUQUD, 2023)
Spaylatter is a form of official loan provided by Shopee. This feature that carries the concept of "Buy now, pay later" allows people to enjoy the opportunity to use credit installments without having to have a credit card. However, legal issues arise in the perspective of Islamic law when these financial instruments are equipped with interest instruments, that is, when the borrower returns the loan, he is required to add to the principal loan. In the perspective of muamalah fiqh, the addition of the loan principal can be categorized as usury. The type of research used in this research is quantitative research, using a research instrument in the form of a questionnaire. With multiple regression analysis involving variable X, namely: x1 knowledge of usury law, x2 knowledge of the shopeepaylatter application and variable Y of buying and selling contracts. The results showed that the t count was 2.163 where the t count was greater than t table (2.163 > 1.67655) with a significant value of 0.036.